Iron-Based Alloys as Catalysts for CO2 Hydrogenation - Mullins, Christopher (Department of Chemical Engineering, 2023)
Use of CO2 as a chemical feedstock in a wide range of applications has been postulated as a method to reduce its concentrations in the atmosphere, in an effort to combat climate change. An especially attractive use of CO2 is its hydrogenation to hydrocarbon fuels. If coupled with a source of renewably generated H2, this reaction could provide a source of carbon neutral energy that can be readily integrated with current infrastructure. This study looked at the performance of a range of iron-based bimetallic catalysts in promoting CO2 hydrogenation. Specifically, iron-nickel, iron-cobalt and iron-copper supported on βsilicon carbide were studied. It had been reported that these materials were more active and selective towards long chain hydrocarbons than their pure metal counterparts, although the reason was unclear. It was hypothesized that alloy formation in these materials would supresses carbide formation, in turn enhancing CO2 activation and hence reaction performance. The catalysts were synthesized using an ammonium hydroxide modified benzyl alcohol technique, which yielded ferrite nanoparticles below 10 nm with narrow size distribution. These ferrites were supported on silicon carbide via a suspension-deposition technique. In total five catalysts were synthesized – two iron-cobalt, two iron-nickel and one iron-copper. All catalysts were synthesized with a molar ratio of two iron to one counter-metal. The catalysts generally had average particle diameters of 6 nm, with one of the iron-nickel catalysts and the ironcopper catalyst slightly smaller at 3 nm and 2 nm respectively. The supported ferrites were reduced in order to yield the active metallic phase. It was shown via in situ characterization that a body centred cubic (BCC) alloy formed in the iron-cobalt samples (final size of 15 nm), while the iron-nickel samples were comprised of two alloy allotropes, with BCC and face centred cubic (FCC) crystalline structures (final size of 10 nm). The iron-copper sample reduced into pure iron (final size 20 nm) and copper phases. The increased size of the metallic phases compared to the freshly synthesized catalysts was due to sintering of the nanoparticles during reduction. In situ reaction studies showed that the iron-cobalt alloys were remarkably stable, with almost no changes in metallic phase seen. The iron-nickel samples were more readily changed by the reactant gases, with the BCC iron-nickel alloy converted to nickel-containing Hägg carbide. The FCC iron-nickel alloy remained unchanged, however. The iron-copper sample, which demonstrated no alloy formation, had its iron phase completely converted to Hägg carbide. Alloying of iron was thus shown to supress carbide formation. Reaction performance of all catalysts to long-chain hydrocarbons was poor when compared to similar materials tested in the literature, with conversions in the range of 4% - 8%. The product distribution was also undesirable, with the majority of product carbon reporting to CO in all five catalysts. Of the hydrocarbons formed, 80% - 96% reported to undesirable methane, depending on the counter metal used. It seemed that iron carbide in the iron-copper catalyst favoured longer chain hydrocarbon production when compared to the more metallic cobalt- and nickel-containing samples (which produced far more methane), but struggled to activate CO2 past CO. While the iron-cobalt catalysts seemed to facilitate more activation of CO2 to hydrocarbons, they showed less potential in forming longer chain hydrocarbons. The two iron-nickel catalysts behaved differently; one catalyst had a stable FCC phase, while its BCC alloy phase was completely converted to carbides, and favoured mostly methane formation. The other catalyst had a similarly stable FCC phase, but also maintained an appreciable BCC alloy fraction, and showed far more propensity to form longer chain hydrocarbons. This catalyst was still not as successful in promoting chain growth as its ironcopper counterpart, however. When comparing performance of the iron-cobalt and -copper catalysts, it seemed that carbide formation was beneficial in encouraging hydrocarbon chain growth, but detrimental to CO2 activation. On the other hand, the iron-nickel catalysts demonstrated that the BCC alloy phase was required to encourage chain growth, while the carbide resulting from its conversion diminished this. These results indicated that an improvement in the activation of CO2 did not necessarily increase hydrocarbon chain length, and that while carbides may be desirable for encouraging longer chain molecules, the presence of nickel in the carbide spoils the effect, at least in the range of temperatures tested. These results led to rejection of the hypothesis that alloys resulted in bimetallic catalysts' improved performance. They indicated that iron carbides are required for stable conversion of CO2 to longer chain hydrocarbons, but that the carbides alone were not extremely active nor selective. It is therefore likely that the counter metal's role in enhancing activity and selectivity at more dilute concentrations is by modulating the carbide phase. It is thus suggested that the impacts of counter metals in more iron-rich systems be studied, where carbide formation would be more facile. Additionally, the difficulty which the catalysts had in activating CO2 could be mitigated by promotion and use of an active support.